The Role of Informal Entrepreneurship Education in Cultivating the Entrepreneurial Spirit and Economic Independence of the Young Generation - Nurhayani Nurhayani; Sumiati Tahir; Hasisa Haruna; Nurwahida Nurwahida; Hardiyanti Ridwan (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose: This study examines the role of informal entrepreneurship education in fostering entrepreneurial spirit and economic independence among young people. The topic is important because entrepreneurial values are not only developed through formal education but also shaped through family, community, and everyday life experiences. Design/methodology/approach: This study uses a library research approach by reviewing relevant literature on entrepreneurship education, informal learning, and entrepreneurial character development. The analysis focuses on how informal educational settings contribute to the formation of entrepreneurial values and independent economic behavior among the younger generation. Findings/Results: The findings show that informal entrepreneurship education has an important role in developing entrepreneurial characteristics such as creativity, risk-taking, adaptability, independence, and responsibility. Family and community environments function as effective spaces for introducing and strengthening entrepreneurial values from an early age. Originality/Value: This study highlights the strategic contribution of informal entrepreneurship education in shaping entrepreneurial spirit and economic independence among young people. The findings imply that stronger collaboration between families, communities, and educational institutions is needed to create a generation that is more independent and entrepreneurial.